Barriers in Fieldwork Practice for Social Work Students: Challenges and Pathways for Reform - Woli, Lokendra (International Research Journal of MMC, 2025)
Fieldwork practice assists on the basis of social work education, helping as the connection between theoretical knowledge and practical application. Despite its significance, social work trainees often face challenges that limit the effectiveness of field education. This study explores the barriers faced during fieldwork practice and identifies pathways for reform. A qualitative exploratory research design was adopted, involving 11 students from different semesters and backgrounds who had completed at least one field placement, purposively selected for this study, guided by data saturation. In 2025, primary data were collected through semi-structured interviews and focus group discussion and thematically analyzed, completed by secondary data from previous literature. Findings exposed multiple barriers, including inadequate supervision, limited and inequitable placement opportunities, financial constraints, weak coordination between universities and field agencies, and cultural or community-based challenges. These obstacles often hinder students’ confidence, learning outcomes, and professional readiness. However, students also identified valuable learning experiences such as improved communication, counseling skills, and professional identity development. Suggested reforms included structured supervision, expansion of placement opportunities, particularly in rural and community-based settings, financial stipends, institutional monitoring, and stronger collaboration between universities and field agencies. The study concludes that systemic reforms are essential to improve the accessibility, equity, and quality of field education. Strengthening supervision, diversifying placements, and ensuring financial and institutional support can better prepare social work students for professional roles, ultimately improving the overall quality and impact of social work education. In this study will benefit students, educators, and institutions by enhancing field placement experiences.